Cryptocurrencies as Digital Payment Media: Opportunities and Challenges - Denny Denny; Hari Sutra Disemadi (Universitas Muhammadiyah Surakarta, 2022)
Cryptocurrency is a centralised network currency system that can connect users without intermediaries or third parties such as banks or governments. Countries globally have different attitudes in drafting regulations regarding cryptocurrencies; some accept, reject, or are neutral. The application of cryptocurrency as a payment medium has not yet been regulated in Indonesian legal jurisdiction. However, cryptocurrencies have various opportunities that can positively impact the country's economy. Indonesia must face various challenges in implementing cryptocurrency as payment. This study examines the opportunities and challenges of implementing cryptocurrency as a payment medium by using a responsive legal theory review. The study was carried out using doctrinal research methods. Indonesia's cryptocurrencies currently do not have a lex specialist (particular regulation). However, the application of cryptocurrency as a payment medium can increase e-commerce transactions, have a payment system with high confidentiality and security, and fast, precise, and low-cost transactions. The challenges that must be implemented are developing institutions and legal constitutions that regulate cryptocurrencies as a payment medium, developing blockchain systems and their application in cellular technology.